GreenCUT&RUN: Efficient Genomic Profiling of GFP‐Tagged Transcription Factors and Chromatin Regulators. Issue 10 (13th October 2021) - Koidl, Stefanie; Timmers, H. T. Marc
Abstract: Genome‐wide mapping of transcription factors and chromatin regulators is important to distinguish their direct from indirect effects on gene transcription or chromatin function. Novel approaches for studying their genomic localization under native conditions, such us cleavage under target and release using nuclease (CUT&RUN), offer higher resolution and lower sequencing costs than classical chromatin immunoprecipitation (ChIP) assays, and require fewer cells but they still depend on the availability of high‐quality antibodies. Here, we describe detailed and robust protocols for greenCUT&RUN, which is a generic CUT&RUN‐based approach for mapping the genome‐wide localization of green fluorescent protein (GFP)‐tagged factors in intact mammalian cells. The greenCUT&RUN method makes use of a micrococcal nuclease (MNase) coupled to a high affinity nanobody against GFP, which exploits the accessibility of multiple surfaces of the GFP tag, thus eliminating issues of antibody variability and availability. We also provide efficient protocols for the expression and purification of two different GFP nanobodies, which recognize non‐overlapping GFP epitopes and can be combined for a further gain in sensitivity and accuracy. Compared to traditional CUT&RUN, genomic localization by greenCUT&RUN reduces handling time and experimental variability. GreenCUT&RUN is a versatile, robust, and universal procedure for surveying the genome‐wide localization of GFP‐tagged versions of proteins that drive key transcriptional programs and regulate chromatin function. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Standard greenCUT&RUN for GFP‐tagged proteins in mammalian cells Alternate Protocol : High‐Ca ++ /low‐salt greenCUT&RUN for GFP‐tagged histone proteins in mammalian cells Support Protocol : Expression and purification of GFP nanobody‐MNase fusion proteins for greenCUT&RUN